Cross-sectional study on awareness and usage of Government COVID-19 mobile health applications among adult smartphone users of Assam - Madhur Borah; Chandana Deka (Apollo Medicine)
Background: As the COVID pandemic became an emergency situation in India, government COVID-19 mobile health (mHealth) apps through smartphones and mobile internet reached citizens across the country and catered to their health needs. Data available from Assam and North Eastern states of India regarding the COVID-19 mHealth apps Arogya Setu app and CoWIN portal, their awareness, usage, and its effectiveness among the general population were very less. Therefore, this study was done with the objectives to find out the awareness and usage of Government COVID-19 mHealth apps among the adult smartphone users of Assam. Methodology: The study was conducted through an online survey method using the Google forms. A total of 310 adult smartphone users from eight different districts of Assam were selected by the convenient sampling method. Data processing and statistical analysis was done using the MS Excel platform. Five-point Likert scale was used for the measurement of respondents' opinions. Results: The awareness level was found to be more than 90%. On user experience of the government mHealth apps, 70% of the respondents agreed that these apps were easy to use and navigate. The satisfaction level of the respondents regarding the apps was found to be high and 80% of study participants trusted the apps. Conclusion: Our study observed that awareness and usage of the government COVID-19 health applications were high among the study participants.